Three-Dimensional Magnetic Resonance Imaging of Velopharyngeal Structures. (Journal of Speech, Language & Hearing Research, 2011)
Purpose: To report the feasibility of using a 3-dimensional (3D) magnetic resonance imaging (MRI) protocol for examining velopharyngeal structures. Using collected 3D MRI data, the authors investigated the effect of sex on the midsagittal velopharyngeal structures and the levator veli palatini (levator) muscle configurations. Method: Ten Caucasian healthy adults (5 women and 5 men) participated. A whole-head 3D MRI scan was obtained while participants were at rest in the supine position. Basic anatomic parameters of the velopharynx including midsagittal velopharyngeal structures and levator muscle configurations were compared between sexes. Results: Detailed information on the 3D MRI protocol and data analysis method was introduced in the study. On the basis of the data, only the length of the levator muscle showed a statistically significant sex difference: Male participants had significantly longer levator muscles than those of female participants. Conclusions: The present study successfully demonstrated the use of 3D MRI in quantifying major velopharyngeal structures and provided additional data on the anatomic variations that exist in healthy adult individuals.